Peranan Bahan Organik dalam Peningkatan Efisiensi Pupuk Anorganik dan Produksi Kedelai Edamame (Glycine max L. Merill) pada Tanah Subgroup Vertic Epiaquepts Pegok Denpasar - I NYOMAN DIBIA; I WAYAN DANA ATMAJA (Agrotrop : Journal on Agriculture Science, 2017)
Role in Increasing Efficiency Organic Fertilizers Inorganic Fertilizer and Soybean Production Edamame (Glycine max L. Merill) on The Ground in Subgroup Vertic Epiaquepts at Pegok Denpasar. The study entitled "The Role of Organic Materials In Inorganic Fertilizer Efficiency Improvement and Edamame Soybean Production In subgroup Vertic Epiaquepts" conducted from July to October 2016 at the Faculty of Agriculture Experimental Farm UNUD to design a randomized block design (RBD). The treatments tested were: 1) P0 = control (without fertilizer); 2) P1 = standard NPK fertilizer (300 kg/ha Phonska); 3) P2 = 5 t/ha petroganik + 50% NPK 4) P3 = 10 t/ha petroganik + 50% NPK; 5) P4 = 15 t/ha petroganik. The results showed that the treatment tested significantly affected parameters: plant height maximum, the number of branches/clump, number of pods containing/clump,the percentage of pods containing/clump, production pods contain/plot, heavy berangkasan fresh/clump, and the estimated production of peas contains /ha. Estimated production of pods contain/ha in a row from the highest are: P3 (22.45 tonnes/ha), P4 (17.73 tonnes/ha), P2 (17.01 tonnes/ha), P1 (16.63 tons/ha), and P0 (10.80 tonnes/ha). Agronomic efficiency indicated by the RAE in each treatment were tested in order are: P3 = 199.83%, P4 = 118.87%, P2 = 103.50%. When compared with the standard fertilizer treatment (P1), the P3 increased efficiency of 99.83%, in P2 by 3.5%, and in P4 amounted to 18.8%.